2016
DOI: 10.1177/1947603516646161
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Chemically Processed Decellularized Meniscal Allografts

Abstract: Objective. The aim of this study was to evaluate the chondroprotective effect of chemically decellularized meniscal allografts transplanted into the knee joints of adult merino sheep. Methods. Lateral sheep meniscal allografts were chemically processed by a multistep method to yield acellular, sterile grafts. The grafts were transplanted into the knee joints of sheep that were treated by lateral meniscectomy. Joints treated by meniscectomy only and untreated joints served as controls. The joints were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…44 Only a few reports have shown recellularization of menisci. 45 For example, Gelse et al 46 transplanted chemically processed decellularized meniscus into merino sheep. They evaluated the cell infiltration into transplanted menisci, but the recellularization was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…44 Only a few reports have shown recellularization of menisci. 45 For example, Gelse et al 46 transplanted chemically processed decellularized meniscus into merino sheep. They evaluated the cell infiltration into transplanted menisci, but the recellularization was insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the sheep as an animal model for osteoarthritis requires the surgical induction of the disease to ensure the development of moderate to severe cartilage damages (Little et al, ). For example, in a lateral meniscectomy model, average OARSI scores can reach up to 16 ± 3 for cartilage (with erosion of cartilage and loss of proteoglycans to the mid/deep zone), associated with moderate synovitis and osteophytes in the lateral femoral and tibial condyles (Gelse et al, ). Obviously, such cases were not identified in the current population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, laboratory-based studies have developed regenerative scaffolds that utilize decellularized meniscus ECM. Examples include using the whole piece of lyophilized tissue directly as a graft [15][16][17], reconstituting pulverized tissue into porous or hydrogel constructs [18][19][20], 3D printing with ECM-based bioinks [21][22][23][24][25], electrospinning from solutions containing natural structural proteins similar to those present in the meniscus ECM [26][27][28], or a combination of the above strategies [29,30]. Many of the studies have demonstrated improved meniscus cell or stem cell viability, infiltration, and neo-matrix deposition over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are limitations associated with each of the above approaches. In the cases of decellularized whole meniscus transplantation, inadequate mechanical strength could lead to construct ruptures and joint deterioration, and insufficient recellularization could hamper chrondroprotective effects [15, 17]. While building bioactive scaffolds reconstituted from ECM components on hydrogel extrusion or casting platforms could provide more flexibility in terms of matching the gaps in various meniscus tears, the substrate stiffness and porosity need to be meticulously tuned to encourage cell spreading and migration [18, 20].…”
Section: Introductionmentioning
confidence: 99%